Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the equation of the tangent line to the curve [tex]\( x^{2/3} + y^{2/3} = 4 \)[/tex] at the point [tex]\((-3\sqrt{3}, 1)\)[/tex], we will use implicit differentiation and find the slope at the given point, and then form the equation of the tangent line.
### Step-by-Step Solution:
1. Implicit Differentiation:
Begin by differentiating the given equation [tex]\( x^{2/3} + y^{2/3} = 4 \)[/tex] implicitly with respect to [tex]\( x \)[/tex].
[tex]\[ \frac{d}{dx}(x^{2/3} + y^{2/3}) = \frac{d}{dx}(4) \][/tex]
Differentiating term by term:
[tex]\[ \frac{d}{dx}(x^{2/3}) + \frac{d}{dx}(y^{2/3}) = 0 \][/tex]
Using the chain rule for the second term:
[tex]\[ \frac{2}{3}x^{-1/3} + \frac{2}{3}y^{-1/3} \frac{dy}{dx} = 0 \][/tex]
2. Solve for [tex]\(\frac{dy}{dx}\)[/tex] (Slope of Tangent Line):
Isolate [tex]\(\frac{dy}{dx}\)[/tex]:
[tex]\[ \frac{2}{3}x^{-1/3} = -\frac{2}{3}y^{-1/3} \frac{dy}{dx} \][/tex]
Simplify:
[tex]\[ x^{-1/3} = -y^{-1/3} \frac{dy}{dx} \][/tex]
Divide both sides by [tex]\( -y^{-1/3} \)[/tex]:
[tex]\[ \frac{dy}{dx} = -\frac{x^{-1/3}}{y^{-1/3}} \][/tex]
Rewrite it with positive exponents:
[tex]\[ \frac{dy}{dx} = -\frac{y^{1/3}}{x^{1/3}} \][/tex]
3. Calculate the Slope at the Given Point [tex]\( (-3\sqrt{3}, 1) \)[/tex]:
Substitute [tex]\( x = -3\sqrt{3} \)[/tex] and [tex]\( y = 1 \)[/tex] into the slope expression:
[tex]\[ \left.\frac{dy}{dx}\right|_{(-3\sqrt{3}, 1)} = -\frac{(1)^{1/3}}{(-3\sqrt{3})^{1/3}} \][/tex]
Simplify the slope calculation:
[tex]\[ (1)^{1/3} = 1 \][/tex]
[tex]\[ (-3\sqrt{3})^{1/3} = -\sqrt[3]{27} = -3^{1/3} \cdot (\sqrt{3})^{1/3} = -3 \cdot \sqrt[3]{3} \][/tex]
Therefore, the slope is:
[tex]\[ \left.\frac{dy}{dx}\right|_{(-3\sqrt{3}, 1)} = -\frac{1}{-3\sqrt[3]{3}} = \frac{1}{3\sqrt[3]{3}} \][/tex]
4. Equation of the Tangent Line:
The equation of a tangent line in point-slope form is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Where [tex]\( (x_1, y_1) \)[/tex] is the point [tex]\( (-3\sqrt{3}, 1) \)[/tex] and [tex]\( m \)[/tex] is the slope calculated above:
[tex]\[ y - 1 = \frac{1}{3\sqrt[3]{3}}(x + 3\sqrt{3}) \][/tex]
Simplify the equation:
[tex]\[ y - 1 = \frac{1}{3\sqrt[3]{3}} x + \frac{1}{3\sqrt[3]{3}} \cdot 3\sqrt{3} \][/tex]
Since [tex]\( \frac{1}{3\sqrt[3]{3}} \cdot 3\sqrt{3} = 1 \)[/tex]:
[tex]\[ y - 1 = \frac{1}{3\sqrt[3]{3}} x + 1 \][/tex]
Add 1 to both sides:
[tex]\[ y = \frac{1}{3\sqrt[3]{3}} x + 2 \][/tex]
Thus, the equation of the tangent line to the curve [tex]\( x^{2/3} + y^{2/3} = 4 \)[/tex] at the point [tex]\((-3\sqrt{3}, 1)\)[/tex] is:
[tex]\[ y = \frac{1}{3\sqrt[3]{3}} x + 2 \][/tex]
### Step-by-Step Solution:
1. Implicit Differentiation:
Begin by differentiating the given equation [tex]\( x^{2/3} + y^{2/3} = 4 \)[/tex] implicitly with respect to [tex]\( x \)[/tex].
[tex]\[ \frac{d}{dx}(x^{2/3} + y^{2/3}) = \frac{d}{dx}(4) \][/tex]
Differentiating term by term:
[tex]\[ \frac{d}{dx}(x^{2/3}) + \frac{d}{dx}(y^{2/3}) = 0 \][/tex]
Using the chain rule for the second term:
[tex]\[ \frac{2}{3}x^{-1/3} + \frac{2}{3}y^{-1/3} \frac{dy}{dx} = 0 \][/tex]
2. Solve for [tex]\(\frac{dy}{dx}\)[/tex] (Slope of Tangent Line):
Isolate [tex]\(\frac{dy}{dx}\)[/tex]:
[tex]\[ \frac{2}{3}x^{-1/3} = -\frac{2}{3}y^{-1/3} \frac{dy}{dx} \][/tex]
Simplify:
[tex]\[ x^{-1/3} = -y^{-1/3} \frac{dy}{dx} \][/tex]
Divide both sides by [tex]\( -y^{-1/3} \)[/tex]:
[tex]\[ \frac{dy}{dx} = -\frac{x^{-1/3}}{y^{-1/3}} \][/tex]
Rewrite it with positive exponents:
[tex]\[ \frac{dy}{dx} = -\frac{y^{1/3}}{x^{1/3}} \][/tex]
3. Calculate the Slope at the Given Point [tex]\( (-3\sqrt{3}, 1) \)[/tex]:
Substitute [tex]\( x = -3\sqrt{3} \)[/tex] and [tex]\( y = 1 \)[/tex] into the slope expression:
[tex]\[ \left.\frac{dy}{dx}\right|_{(-3\sqrt{3}, 1)} = -\frac{(1)^{1/3}}{(-3\sqrt{3})^{1/3}} \][/tex]
Simplify the slope calculation:
[tex]\[ (1)^{1/3} = 1 \][/tex]
[tex]\[ (-3\sqrt{3})^{1/3} = -\sqrt[3]{27} = -3^{1/3} \cdot (\sqrt{3})^{1/3} = -3 \cdot \sqrt[3]{3} \][/tex]
Therefore, the slope is:
[tex]\[ \left.\frac{dy}{dx}\right|_{(-3\sqrt{3}, 1)} = -\frac{1}{-3\sqrt[3]{3}} = \frac{1}{3\sqrt[3]{3}} \][/tex]
4. Equation of the Tangent Line:
The equation of a tangent line in point-slope form is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Where [tex]\( (x_1, y_1) \)[/tex] is the point [tex]\( (-3\sqrt{3}, 1) \)[/tex] and [tex]\( m \)[/tex] is the slope calculated above:
[tex]\[ y - 1 = \frac{1}{3\sqrt[3]{3}}(x + 3\sqrt{3}) \][/tex]
Simplify the equation:
[tex]\[ y - 1 = \frac{1}{3\sqrt[3]{3}} x + \frac{1}{3\sqrt[3]{3}} \cdot 3\sqrt{3} \][/tex]
Since [tex]\( \frac{1}{3\sqrt[3]{3}} \cdot 3\sqrt{3} = 1 \)[/tex]:
[tex]\[ y - 1 = \frac{1}{3\sqrt[3]{3}} x + 1 \][/tex]
Add 1 to both sides:
[tex]\[ y = \frac{1}{3\sqrt[3]{3}} x + 2 \][/tex]
Thus, the equation of the tangent line to the curve [tex]\( x^{2/3} + y^{2/3} = 4 \)[/tex] at the point [tex]\((-3\sqrt{3}, 1)\)[/tex] is:
[tex]\[ y = \frac{1}{3\sqrt[3]{3}} x + 2 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.